2012
DOI: 10.1002/lary.23451
|View full text |Cite
|
Sign up to set email alerts
|

Modulating phonation through alteration of vocal fold medial surface contour

Abstract: Objectives 1. To test whether alteration of the vocal fold medial surface contour can improve phonation. 2. To demonstrate that implant material properties affect vibration even when implant is deep to the vocal fold lamina propria. Study Design Induced phonation of excised human larynges. Methods Thirteen larynges were harvested within 24 hours post-mortem. Phonation threshold pressure (PTP) and flow (PTF) were measured before and after vocal fold injections using either calcium hydroxylapatite (CaHA) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…This is a question that many have tried to answer, and, as a result, the way in which we do injection laryngoplasty and the shape of our thyroplasty implants have evolved. 1,17,18 Titze found that a divergent prephonatory glottal configuration achieved lower oscillation threshold pressures correlating with greater ease of phonation. 3 However, other studies using physical models and numerical studies showed that the lowest phonation threshold pressure occurs for a rectangular or slightly convergent glottis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a question that many have tried to answer, and, as a result, the way in which we do injection laryngoplasty and the shape of our thyroplasty implants have evolved. 1,17,18 Titze found that a divergent prephonatory glottal configuration achieved lower oscillation threshold pressures correlating with greater ease of phonation. 3 However, other studies using physical models and numerical studies showed that the lowest phonation threshold pressure occurs for a rectangular or slightly convergent glottis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Mau et al predicted that increasing vertical thickness (ie, glottal channel height) of the vocal folds and a more rectangular glottal geometry would lower phonation threshold pressure and flow. 1 Further, Courey tested injection material into different locations within the glottis and found that placement of graft in the medial aspect of the TA muscle reduced the forces necessary to bring the vocal folds into position for vibration. 17 The histology from that report also appeared to approximate a rectangular glottis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laryngectomy is a surgical removal of the larynx for the treatment of laryngeal or other oral cavity cancers [1]; therefore, persons after laryngectomy lose their ability to produce speech sounds and suffer in their daily communication [2], [3]. Although there are several options to assist the speech communication for those patients such as esophageal speech, trachea-esophageal speech, and electrolaryngeal speech, these approaches generally produce an abnormal sounding voice with a pitch that is aberrantly low and limited in range [4].…”
Section: Introductionmentioning
confidence: 99%
“…People who have their larynx (vocal fold) impaired due to physical impairment or treatment of laryngeal cancer suffer during their daily life. A surgery can help these patients reconstruct or repair their larynx, but their phonation can hardly be completely recovered [1]. Patients with surgically reconstructed larynx generally have problems in controlling laryngeal functions, thus producing whispered speech with extreme hoarseness [2].…”
Section: Introductionmentioning
confidence: 99%